Significant factors in rectal cancer recurrence - Lazarova, Ana (Longdom group, 2020)
INTRODUCTION The incidence of recurrence of rectal cancer worldwide has shown a significant decline in the last ten years due to the progress of neoadjuvant preoperative chemoradiotherapy and the improvement of surgery. The recurrence rate is 4% - 8% usually in the first 3 years after surgical treatment. AIM OF THE STUDY This paper demonstrate the importance of the significant factors which has influence in the recurrence of rectal cancer in order to provide increase in 5-year survival rate and decrease in recurrence rate in operated patients from rectal cancer. MATERIAL AND METHODES This is a prospective study which include a 82 patients aged from 43 to 87 years, with an average age of 66 years with previously colonoscopy proven rectal cancer. Before the operation magnetic resonance images (MRI) was made at - 1.5 T magnet for MRI staging preoperatively. In the three years fallow up period after the operation when suspicion of local recurrence was established control MRI was done. Waited images which were made are: SAG T2 WI, AX T1WI, AX T2WI, AX DWI, and SAG and AX waited images after intra venous contrast medium administration - Gadolinium. RESULTS In three years fallow up period after the operation 13.4% (11) patients had a recurrence of the disease. The disease recurred in 14.6% (7) male patients, and in 11.8% (4) female patients. The occurrence of recurrence of the disease was not significantly related to the age of the subjects (p = 0.28). Patients with relapse were on average insignificantly older than patients without relapse (69.6±8.5vs.66.2±9.9). The results of the study showed that the occurrence of recurrences was significantly associated with extra mural vascular invasion (EMVI) determined pathohistologically (p = 0.018). With recurrence were registered 81.8% (9) patients EMVI positive and 18.2% (2) patients EMVI negative. In the group of patients without relapse, 43.7% (31) patients were EMVI positive, 56.3% (40) were EMVI negative patients. Five from the patients with recurrence were at patohistology T3 stage and four were at T4 stage, and only two of them were at T2 stage but with positive EMVI. Depending on the nodal stages there were 14.6 %( 6) patients with rectal cancer recurrence in N0 stage, 16 %( 4) patients in N1 stage and one patient in N2 stage of the disease CONCLUSION The results of the study showed that the occurrence of recurrences of rectal cancer was significantly associated with extra mural vascular invasion determined pathohistologically (p =0.018). Risk factors for local recurrence included: positive circulatory resection margins, lack of preoperative neoadjuvant treatment in advanced disease, positive extramural vascular invasion, tumor perforation during surgical treatment, tumor localized next to the anal verge.
Keywords: rectal cancer recurrence; MRI; EMVI; tumor staging